44 Service evaluation of the use of fluids at end of life across two inpatient palliative care units. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Brocklebank, Jenny; Pitsillides, Constantina; Liddle, Olivia; Sheehan, Roseleen; Parry, Rachel; Fingas, Samuel; Smith, Eleanor
Abstract : Background: 'Five Priorities of Care' requires an individualised plan for hydration at end of life and discussion with patients/those important to them. However there is little research surrounding this topic and the use of fluids is often dependent upon the individual prescriber. Methods: A service evaluation of the current practice in Sheffield's inpatient palliative care units. A retrospective case-note review of deceased patients over a two-month period at St Luke's Hospice (SLH) and Macmillan Palliative Care Unit (MPCU), 37 and 20 cases respectively. A qualitative staff survey of individual thoughts and practices with fluids. Results: Consistently good documentation of discussions about hydration risks and benefits, but less for symptoms of dry mouth and mouth care. These discussions were documented more often at SLH than MPCU (97/81% vs 60/35%). MPCU offered and prescribed fluids 2.5 times more often. Most commonly prescribed 1 litre of normal saline over 24 hours. Most common reason for stopping fluids was skin pooling (75% SLH) and secretions (89% MPCU). Documentation of discussions surrounding this seen for all cases SLH, 50% cases MPCU. An inability to quench thirst ranked first on survey regarding reasons for fluid delivery, opposed to dry mouth in clinical practice. Opinion was that the likely benefit from fluids was almost equal to the risk of harm. Subcutaneous delivery was the preferred route for being less invasive. Conclusions: Hydration at end of life needs to be individualised and regularly reviewed. Documentation was higher at SLH than MPCU regarding fluids, due to the ADD CARING pneumonic. Steps have been made at MPCU to prompt consideration of fluids at end of life. Improved documentation needed for dry mouth symptoms/mouth care. Staff responses did not always correspond to documented reasons for initiating and stopping fluids, suggesting these need to be decisions made across the MDT.